The Differences Between RSV and no RSV Acute Bronchiolitis in Hospitalized Infants: A Cross-Sectional Study - Evangelos Christou; Evangelos Bourousis MD; Avraam Pouliakis PhD; Konstantinos Douros Prof; Pinelopi Varela; Dimitris Delis PhD; Kostas N. Priftis Prof (SAGE Publishing, 2022)
To identify the differences between the RSV and non-RSV bronchiolitis in hospitalized infants in a Greek tertiary pediatric unit and the possible risk factors related to severe forms of the illness. We performed a retrospective cross-sectional data analysis by reviewing medical records of patients that were hospitalized for acute bronchiolitis from 2012 to 2019. The patients with RSV bronchiolitis were found to require antibiotic treatment, IV fluids, adrenaline, and hypertonic saline inhalations more frequently than the non-RSV patients. They also required prolonged hospitalization, especially those that were admitted to PICU, and received oxygen therapy for longer periods. We searched risk factors for severe forms of the disease according to the need for admission to PICU, the supplemental oxygen and the extended length of hospital stay, concurrently. The patients with RSV bronchiolitis developed more severe illness in comparison with patients with bronchiolitis due to other respiratory viruses.